SP8 Transcriptional Regulation of Cyclin D1 During Mouse Early Corticogenesis - Borello, Ugo; Berarducci, Barbara; Delahaye, Edwige; Price, David J.; Dehay, Colette (Frontiers in Neuroscience, 2018)
Multiple signals control the balance between proliferation and differentiation of neural progenitor cells during corticogenesis. A key point of this regulation is the control of G1 phase length, which is regulated by the Cyclin/Cdks complexes. Using genome-wide chromatin immunoprecipitation assay and mouse genetics, we have explored the transcriptional regulation of Cyclin D1 (Ccnd1) during the early developmental stages of the mouse cerebral cortex. We found evidence that SP8 binds to the Ccnd1 locus, specifically on exon regions. In vitro experiments show a specific SP8 activity on Ccdn1 gene 3’-end, and point to a putative role for SP8 in modulating PAX6-mediated repression of Ccnd1 along the dorso-ventral axis of the developing pallium, creating a mediallow-lateralhigh gradient of neuronal differentiation. Activation of Ccnd1 through the promoter/5’-end of the gene does not depend on SP8, but on ßcatenin (CTNNB1). Importantly, alteration of the Sp8 level of expression in vivo affects Ccnd1 expression during early corticogenesis. Our results indicate that Ccnd1 regulation is the result of multiple signals and that SP8 is a player in this regulation, revealing an unexpected and potentially novel mechanism of transcriptional activation.